Pembuatan alat ukur kadar gula darah berdasarkan tingkat kekeruhan spesimen urin menggunakan sensor warna TCS230 dan photodioda dengan tampilan LCD (An instrument for blood sugar level based on the turbidity level of the urine specimen using a TCS230 color sensor and a photodiode with an LCD display) - Zalmirda Pratiwi; - Hufri (Department of Physics – Universitas Negeri Padang UNP, 2020)
Blood sugar levels are a major factor of diabetes. Diabetes is a one of a dangerous diseases caused by damage to the working system of the hormone insulin in the body’s metabolism. The diagnosis of blood sugar levels is generally by pricking a finger or arm to take a sample of the patient’s blood. Another method can be used without hurting the patient’s body, which is using a urine sample. Discoloration of the patient’s urine can be detected using the TCS230 color sensor and photodiode. The design of the tool system in this research uses the changes in the color of the urine specimen as a measurement parameter. This research aims to determine the performance and design specifications of the manufacture of blood sugar levels based on the level of urin turbidity using the TCS230 color sensor and photodiode. There are two research results. First, the result of performance specifications is a beam-shaped measuring device consisting of an object box measuring 8,5x6x8 cm3 and an electronic component box measuring 20x10x10 cm3. Second, the result of design specifications are the precision of the tool at 95,95% with a percentage of errors of 4,44% and accuracy of 99,25%.